Item development for a patient‐reported measure of compassionate healthcare in action - Eleanor Chatburn; Elizabeth Marks; Lucy Maddox (Health Expectations)
Abstract Background Compassionate care is a fundamental component of healthcare today; yet, many measures of compassionate care are subjective in focus and lack clarity around what compassionate care looks like in practice. Measures mostly relate to physical healthcare settings, neglecting mental healthcare. They also lack significant involvement of people with lived experience (PLE) of healthcare delivery in their development. This study aimed to begin the process of developing a new patient‐reported measure, one that captures the observable actions of compassionate care delivery or ‘compassionate healthcare in action’ by any healthcare professional working in any care setting. The study involves PLE of healthcare delivery, both patients and staff, throughout. Methods A multistage mixed‐methods scale development process was followed. First, items were derived inductively from reflexive thematic analysis of patient and clinician interviews about what compassionate care meant to them (n = 8), with additional items derived deductively from a literature review of existing measures. Next, a panel of patient, clinician and researcher experts in compassionate care was recruited (Round 1: n = 33, Round 2: n = 29), who refined these items in a two‐round modified online Delphi process. Results Consensus was reached on 21 items of compassionate care in action relating to six facets: understanding, communication, attention, action, emotional sensitivity and connection. These items will form the basis for further scale development. Conclusions This item development work has laid the foundation of a potential new tool to systematically measure what compassionate healthcare in action looks like to patients. Further research is underway to produce a valid and reliable version of this proposed new measure. We have outlined these initial stages in detail in the hope of encouraging greater transparency and replicability in measure development, as well as emphasising the value of involving PLE throughout the process. Patient or Public Contribution This study involved PLE of both physical and mental healthcare (as staff, patients and service users) throughout the development of the new measure, including initial project conceptualisation and participation in item generation and refinement stages.